LMS Implementation in High Schools in Eastern Indonesia After the Covid-19 Pandemic - Yulianto, Budi; Rita Layona (Journal of Education Technology, 2023)
The Covid-19 pandemic had prevented students and teachers from carrying out teaching and learning activities in physical classroom due to activity restrictions, social distancing, or lockdown. The problem that occurs is the unavailability of an IT-based (online) learning management system in many schools causing the teaching and learning process from outside the school to be delayed. Covid-19 has not only caused a health emergency, but also an educational emergency. This research aimed to develop an LMS and implement it free of charge in several schools in eastern Indonesia and analysed the impact of implementation over 2 years. The research method used is the Prototype Method with the stages of Communication, Modeling, Construction, and Deployment. At the Communication stage, data collection was carried out through interviews with several school parties regarding system requirements. At the Modeling stage, system design is carried out using Class Diagram, Use Case Diagram, Activity Diagram, and Sequence Diagram. At the Construction stage, application development is carried out using the PHP web programming language with a MySQL database. In the Deployment stage, implementation is carried out on the Microsoft Azure Cloud platform. The results of the research shown that the implementation of the LMS provided an increase in score for the exact sciences (Mathematics) and the language sciences (English) fields. As for the field of social sciences (Citizenship) did not show a significant increase.